2021
DOI: 10.3390/biomedicines9091255
|View full text |Cite
|
Sign up to set email alerts
|

When Activator and Inhibitor of PPARα Do the Same: Consequence for Differentiation of Human Intestinal Cells

Abstract: Peroxisome proliferator-activated receptor α (PPARα) is a ligand-dependent transcription factor that plays a role in various processes including differentiation of several cell types. We investigated the role of PPARα in the differentiation of intestinal cells using HT-29 and Caco2 cell lines as a model as well as human normal colon and colorectal carcinoma tissues. We detected a significant increase in PPARα expression in differentiated HT-29 cells as well as in normal surface colon epithelium where different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 72 publications
3
12
0
Order By: Relevance
“…(E) Schematic summary of obtained results. Detected increase in PIP2 observed after fenofibrate, WY-14643, and GW6471 treatment could explain our previous results reported increase in villin expression under the same experimental conditions [18]. The effect of PPARα ligands is illustrated by arrows: green-increase in expression, red-decrease in expression, grey dotted-no effect, red dotted-decrease in expression or no effect (the results differ in HT-29 and Caco2 cell lines).…”
Section: Effect Of Fenofibrate Wy-14643 and Gw6471 On Expression Of P...mentioning
confidence: 56%
See 4 more Smart Citations
“…(E) Schematic summary of obtained results. Detected increase in PIP2 observed after fenofibrate, WY-14643, and GW6471 treatment could explain our previous results reported increase in villin expression under the same experimental conditions [18]. The effect of PPARα ligands is illustrated by arrows: green-increase in expression, red-decrease in expression, grey dotted-no effect, red dotted-decrease in expression or no effect (the results differ in HT-29 and Caco2 cell lines).…”
Section: Effect Of Fenofibrate Wy-14643 and Gw6471 On Expression Of P...mentioning
confidence: 56%
“…Although it has been reported that PPARα plays a role in the differentiation of various cells [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], the differentiation of intestinal cells seems to be PPARα-independent, as shown in our previous study [ 18 ]. In HT-29 and Caco2 cells lines, administration of PPARα activators as well as a PPARα inhibitor increased the expression of villin.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations